2019
DOI: 10.1105/tpc.19.00655
|View full text |Cite
|
Sign up to set email alerts
|

CORRECTION: Two Abscisic Acid-Responsive Plastid Lipase Genes Involved in Jasmonic Acid Biosynthesis in Arabidopsis thaliana

Abstract: In the Methods section of the above publication, the SALK T-DNA insertion line identifiers were stated incorrectly. We also omitted important details describing the construction of triple mutant lines, and the germination assay. Under "Plant Material and Growth Conditions," we mistakenly defined "SALK_1234548 (plip2-1)" and "SALK_134525 (plip2-2)". The correct numbers should be SALK_123548 (plip2-1) and SALK_134251 (plip2-2), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, JAM1 regulates both ABA and JA responses in Arabidopsis (Li et al ., ; Nakata et al ., ). ABA could promote the expression of PLIP2 and PLIP3, which might be involved in initiating JA biosynthesis (Wang et al ., ). In this study, we reveal two mechanisms underlying the crosstalk between JA and ABA: JAZ proteins can physically interact with ABI5 and repress its activity; ABA can induce JA biosynthesis to promote the degradation of JAZ proteins.…”
Section: Discussionmentioning
confidence: 97%
“…For example, JAM1 regulates both ABA and JA responses in Arabidopsis (Li et al ., ; Nakata et al ., ). ABA could promote the expression of PLIP2 and PLIP3, which might be involved in initiating JA biosynthesis (Wang et al ., ). In this study, we reveal two mechanisms underlying the crosstalk between JA and ABA: JAZ proteins can physically interact with ABI5 and repress its activity; ABA can induce JA biosynthesis to promote the degradation of JAZ proteins.…”
Section: Discussionmentioning
confidence: 97%
“…However, S. littoralis infestation does not increase the ABA level in maize shoot (Erb, Flors, et al, 2009), and in rice roots, the biosynthesis of ABA is not induced by belowground D. balteata and L. oryzophilus attack (Lu et al, 2015). Considering the crosstalk between ABA and JA signaling and the role of ABA in drought stress response, it is expected that the ABA pathway is involved in systemic defenses against herbivores (Erb, Flors, et al, 2009; Erb, Köllner, et al, 2011; Wang et al, 2018). A previous study showed that exogenous application of ABA on maize root boosts aboveground defense (Erb, Gordon‐Weeks, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%